ÐšÑ€Ñ–Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¾Ð²Ð°Ð½Ð° Ñ…Ð¾Ñ€Ñ–Ð°Ð»ÑŒÐ½Ð° Ñ‚ÐºÐ°Ð½Ð¸Ð½Ð° Ð² Ñ‚ÐµÑ€Ð°Ð¿Ñ–Ñ— Ð¼Ð°Ñ‚ÐµÑ€Ð¸Ð½ÑÑŒÐºÐ¾-Ð¿Ð»Ð¾Ð´Ð¾Ð²Ð¾Ñ— Ñ–Ð½Ñ„ÐµÐºÑ†Ñ–Ñ— (ÐºÐ»Ñ–Ð½Ñ–ÐºÐ¾-ÐµÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ðµ Ð´Ð¾ÑÐ»Ñ–Ð´Ð¶ÐµÐ½Ð½Ñ) - Prokopyuk, V. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The cryosensitivity of chorionic tissue (CT) under different cryopreservation protocols, CT effect on pregnancy proceeding and outcome in laboratory animals were investigated. The application efficiency of preparation â€œPlatex-chorionicâ€ (PC) in a combined therapy of maternal-fetal infection (MFI) was under study. Both DMSO and that combined with PEO-4000 were shown to be the cryoprotectants of choice for CT freezing. Chorionic tissue has no teratogenic properties and positively affects the reproductive indices. The PC use in a combined therapy of MFI enables to improve placental structure, reduce the morbidity in gestation process and labor, thereby significantly enhancing prognosis for mother and newborn.